2022
DOI: 10.1093/icvts/ivac068
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the dissection properties of ascending thoracic aortic aneurysms

Abstract: OBJECTIVES Presentation, management and outcomes in the aortic dissection (AD) of ascending thoracic aortic aneurysm (ATAA) differ in gender and age. The purpose of this study is to investigate the dissection properties of male and female ATAAs. METHODS Peeling tests were performed to quantitatively determine the delamination strength and dissection energy of 41 fresh ATAA samples (22 males and 19 females) in relatively young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Increased arterial stifness in postmenopausal females could be partly ameliorated by estrogen replacement therapy [20,21]. Tong et al found that age-related decrease of the circumferential and longitudinal delamination strengths in elderly females with ascending aortic aneurysm was more prominent than that in elderly males (>65 years), which indicated that elderly females had a higher propensity for dissection occurrence compared with elderly males [22]. Similarly, GERAADA's study also confrmed a higher incidence of TAAD in females older than 75 years [4].…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial stifness in postmenopausal females could be partly ameliorated by estrogen replacement therapy [20,21]. Tong et al found that age-related decrease of the circumferential and longitudinal delamination strengths in elderly females with ascending aortic aneurysm was more prominent than that in elderly males (>65 years), which indicated that elderly females had a higher propensity for dissection occurrence compared with elderly males [22]. Similarly, GERAADA's study also confrmed a higher incidence of TAAD in females older than 75 years [4].…”
Section: Discussionmentioning
confidence: 99%
“…Older women tend to have stiffer aortas with exaggerated systolic pulse amplification, 7 which may adversely impact hemodynamics, location of intimal tear, and propagation of aortic dissection. The tissue architecture and mechanical properties of the aorta may differ between men and women, 8 predisposing the latter to partial or complete rupture. Indeed, bloodstained pleural effusions were observed more often in women in the present study.…”
mentioning
confidence: 99%